2020
DOI: 10.21070/midwiferia.v6i1.508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family Characteristics on Stunting Events in Toddlers Aged 6-59 Months

Abstract: Stunting is defined as a chronic condition that is a picture of stunted growth due to lack of nutrition in the long run and or due to other problems. Stunting, especially in infants, can slow down both physical and mental development of children, so special attention is needed. Many factors influence the incidence of stunting, including family characteristics such as family economic status, mother's education, parents 'height and parents' level of knowledge about toddler nutrition. The purpose of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
5
0
4
Order By: Relevance
“…Pada dasarnya pemberian imunisasi pada anak memiliki tujuan penting yaitu untuk mengurangi risiko mordibitas dan mortalitas pada anak akibat penyakit-penyakit yang tidak dapat dicegah melalui imunisasi (Izah et al, 2020). Status imunisasi pada anak merupakan salah satu indikator kontak keberhasilan pelayanan kesehatan, karena diharapkan melalui pelayanan kesehatan akan membantu memperbaiki masalah gizi baru, sehingga status imunisasi berdampak secara positif terhadap status gizi balita dalam jangka panjang (Endris et al, 2017).…”
Section: Hubungan Status Imunisasi Dengan Kejadian Stuntingunclassified
“…Pada dasarnya pemberian imunisasi pada anak memiliki tujuan penting yaitu untuk mengurangi risiko mordibitas dan mortalitas pada anak akibat penyakit-penyakit yang tidak dapat dicegah melalui imunisasi (Izah et al, 2020). Status imunisasi pada anak merupakan salah satu indikator kontak keberhasilan pelayanan kesehatan, karena diharapkan melalui pelayanan kesehatan akan membantu memperbaiki masalah gizi baru, sehingga status imunisasi berdampak secara positif terhadap status gizi balita dalam jangka panjang (Endris et al, 2017).…”
Section: Hubungan Status Imunisasi Dengan Kejadian Stuntingunclassified
“…5 The result of this study is also in line with the research that was conducted by Izah et al (2020) which showed that most stunting children cases were found in families with income that was lower than regional minimum wage. 6 Family income is one of the indicators that determines economic status, where high family income can meet family needs, especially diverse food needs so that food intake for children under five is fulfilled. This condition will have an effect on increasing the quality of food consumption for family members and be considered as an overview of good nutritional assessment.…”
Section: Discussion a Family Income During Covid-19 Pandemicmentioning
confidence: 99%
“…On the other hand, the low level of family income results in low household food purchasing power. 6 The low purchasing power of food products results in inadequate fulfillment of the nutritional needs of children under five. 22…”
Section: Discussion a Family Income During Covid-19 Pandemicmentioning
confidence: 99%
“…The purchasing power of families for healthy food is influenced by family income, according to latest research during pandemic, because the type of food to be purchased is determined by the degree of income. The purchase power of a family's food is proportional to its income [11]. It is possible to meet the food needs of all family members with a large salary.…”
Section: Risk Factors On Influential Determinantsmentioning
confidence: 99%